Antecedents of Employee Performance on the Media Nusantara Citra Group Television Station - Fauzan Sadat; B. Medina Nilasari (Business and Entrepreneurial Review, 2022)
This study aims to analyze the effect of Transformational Leadership, Compensation, Organizational Culture on Employee Performance mediated by Job Satisfaction. The data used in this study is primary data taken through the distribution of questionnaires using a purposive sampling method involving employees of the television industry in the MNC group as many as 200 respondents. The analytical tool in this study is Structural Equation Modeling (SEM) using AMOS version 21. The results of this study found that Transformational Leadership, Compensation, Organizational Culture have an influence on Employee Performance and also on Job Satisfaction. In the next result, Job Satisfaction can mediate Transformational Leadership on Employee Performance, Compensation on Employee Performance and Organizational Culture on Employee Performance. From the results of this study, it is suggested to the manager to maintain the level of Employee Performance by increasing the leadership spirit and creating a healthy organization accompanied by employee welfare, so that employees will feel satisfied in carrying out their work.